Tindak Pidana Penyalahgunaan Narkotika Gol I Bagi Diri Sendiri (Studi Kasus Perkara No.631/Pid.Sus/2023/PN.Jkt.Sel) - Sembiring, Berlian Garuda; Myharto, Wiend Sakti (Postulat, 2025)
Narcotics are substances or idrugs obtained from plant or non-plants, either through amixing process or naturaaly.This substances is capable of causing depression, as well as changes in consciousnes and loss of ttaste, reducing and eliminating suffering, thus causing attachment.The aim of the research is to find out or get what happenes at the end of the reserch.The research method uses a qualitative normative juridical method through approaching the court decision in Case No.631/Pid.Sus/2023/PNJkt.Sel and statutory regulations.Result obtained from the Agus Taufik Hidayat case carried out at the Southerm District Court which imposed sanctions in the form of detention and fines. This decission was not wise or appropriate because it did not take into account SEMA No:04 of 2010